Kasih Sayang Guru Dan Penerapannya Perspektif Al-Quran Dan Hadis - Rahmati ati; Syabuddin; Syahminan (Al-Mu'tabar, 2023)
This paper explores the Qur'anic and Hadith's perspective on teaching, emphasizing the principles of tawhid and Ilahiyah in shaping children's character. By embracing the natural potential of children as knowledge and skills, teachers are expected to be able to direct students to answer life's questions. This research uses qualitative methods with the type of library research that is descriptive of the meaning of Rahmah in the Quran which is integrated with teacher competence in managing learning. The results of this study found that teacher affection is important for an educator, not just as a conveyor of information or science. The teacher's compassion, as presented in the Qur'an and Hadith, contains such important elements as patience. The compassionate aspect of teacher compassion creates a learning environment full of warmth and support because the teacher's actions can have a big impact on the formation of student character.